Meta-analysis of the effects of laidlomycin propionate, fed alone or in combination with chlortetracycline, compared with monensin sodium, fed alone or in combination with tylosin, on growth performance, health, and carcass outcomes in finishing steers in North America - Cernicchiaro, Natalia; Corbin, M.; Quinn, M.; Prouty, F.; Branine, M.; Renter, David G. (My University, 2016)
The objective of this research was to use data from multiple studies to comprehensively quantify the effects of feeding 1) laidlomycin propionate (LP), alone and/or in combination with chlortetracycline, compared with 2) monensin sodium (MS), alone and/or in combination with tylosin, at commercially approved dosages, on ADG, DMI, feed efficiency (FE), mortality, and carcass characteristics (HCW and liver abscesses). A secondary objective was to explore potential sources of heterogeneity among the comparative effectiveness studies. A systematic review of peer-reviewed literature and industry reports was used to identify studies that included direct comparisons of these treatments in finishing steers in North America. Random-effects meta-analysis models of performance, carcass, and health-related outcomes were fitted with extracted data, consisting of a total of 17 data sets comprising a total of 135 pens and 13,603 steers. Results showed that pens of steers fed LP had increased ADG (live and carcass adjusted), DMI, and HCW compared with those fed monensin (P < 0.05). However, liver abscesses were more common in LP-fed cattle than in MS-fed cattle (P < 0.05), presumably because of differences in the concurrently fed antimicrobials. No significant effects (P > 0.05) were identified for FE or for health-related outcomes (overall and cause-specific mortality). There was a substantial amount of heterogeneity in outcomes among studies, and when pen size and type of production setting were included in mixed-effects metaregression models, they accounted for only a small proportion of the between-study heterogeneity found in the meta-analysis models. Therefore, caution should be exercised when interpreting summary estimates in the presence of substantial heterogeneity. However, these results provide comprehensive information on the comparative effects of different ionophores across multiple studies and multiple years, states, and production settings. These unique results can enable quantitative and informed decisions by potential end users of these feed additives that are widely used in the U.S. beef industry for reducing the costs of beef production through enhanced cattle performance.
Citation: Cernicchiaro, N., Corbin, M., Quinn, M., Prouty, F., Branine, M., & Renter, D. G. (2016). Meta-analysis of the effects of laidlomycin propionate, fed alone or in combination with chlortetracycline, compared with monensin sodium, fed alone or in combination with tylosin, on growth performance, health, and carcass outcomes in finishing steers in North America. Journal of Animal Science, 94(4), 1662-1676. doi:10.2527/jas2015-0086
Keywords: Feedlot Performance; Finishing Steers; Ionophore; Laidlomycin; Propionate; Meta-Analysis